A light‐mediated study of carotenoids in carrots (Daucus carota) using resonance Raman spectroscopy. (14th June 2021) - Badgujar, Pooja Manik; Wang, Yu‐Chun; Cheng, Chia‐Liang
Abstract: In photosynthetic systems, carotenoids play significant roles, and the prime role is light harvesting, then transferred to the photosynthetic apparatus for photosynthesis. Understanding carotenoids is a significant concern as it has a vital role in photosynthesis, and it also acts as a protective pigment in the biosystem. Carotenoids are widely distributed in almost all photosynthetic biosystems but highly accumulated in carrots, especially in ( Daucus carota ). Therefore, carrots can be a simpler model to understand the formation of carotenoids and their regulation with the help of exposure to sunlight. Raman spectroscopy is a noninvasive method to study molecular signature; it can be an ideal tool to understand carotenoids pigments in the growing stages of carrots. In this work, using resonance Raman spectroscopy with 532‐nm wavelength laser excitation, we were able to detect predominant carotenoid bands such as β ‐carotene, α ‐carotene, and lutein, at 1517–1519 cm −1 and 1521–1524 cm −1 with high peak intensities. This work gives a clear description and evidence of how light plays a profound effect on the activation and regulation of carotenoids. We observed β ‐carotene in the nonphotosynthetic region of the plant, as a photoprotection of developing life is one of the significant roles of carotenoids, and Raman bands of carotenoids can be considered as the biomarker of photoprotection of developing life. Abstract : This study highlights how illumination of light regulates the accumulation of carotenoids and root development in carrot plants. Illustration on how Raman spectroscopic signature of carotenoids obtained from a simple model like carrot helps evidencing complex carotenogenesis at molecular level. Raman signature of carotenoids that can be used as a photoprotection marker in complex biological systems has been discussed.